Impact of Climate Change on Agricultural Production and People’s Reactions in China’s Gansu Province:A Behavioural Economics Interpretation - Wanrong, Chen (2016)
From July 2016 to August 2016, I selected seven survey area and 268 people who plants crops in Gansu province as an example to analyse how behaviour economics model explain the actions of farmers to plant crops because of the climate change and global warming, and the different results between behaviour economics model analysis and standard economic model (deviations), as well as the reasons of the occurrences of these deviations when farmers making judgements and decisions before, during, or after planting crops in agricultural cultivation and agricultural production process. The analytical results based on the survey and sources of climate change indicate that the decisions made by the farmers obey the general rules of behaviour economics, but not the standard economics rule under the conditions of uncertainties. With the impact of cognitive biases and the stereotype for local farmers in thinking pattern, the results deviate systematically from the traditional economic theory. The farmers act irrational when judging and making decisions. And these irrational cause the time lag between adopting and changing of the decisions. There are two majority irrational actions and behaviours that happened frequently. First of all, the farmers make irrational decisions when choosing different types of crops, determining the timing of sale the crops, making the plant scheme for the following years under the impaction of heuristic cognitive biases. Another irrational situations occurs due to the actual situation of China and its inherent characteristics. Under the consideration of making a living and ensure their life, farmers always have a low reference point or low judgement level to determine “gain” or “loss”. This leads to more conservative decision that farmers made when choosing types of crops to be planted. This paper aims at extending the study field of behaviour economic and providing more supports and suggestions for the local crops planting.